Periplasmic Carbonic Anhydrase Structural Gene (Cah1) Mutant in Chlamydomonas reinhardtii - Van, Kyujung (American Society of Plant Physiologists, 1999)
To survive in various conditions of CO(2) availability, Chlamydomonas reinhardtii shows adaptive changes, such as induction of a CO(2)-concentrating mechanism, changes in cell organization, and induction of several genes, including a periplasmic carbonic anhydrase (pCA1) encoded by Cah1. Among a collection of insertionally generated mutants, a mutant has been isolated that showed no pCA1 protein and no Cah1 mRNA. This mutant strain, designated cah1-1, has been confirmed to have a disruption in the Cah1 gene caused by a single Arg7 insert. The most interesting feature of cah1-1 is its lack of any significant growth phenotype. There is no major difference in growth or photosynthesis between the wild type and cah1-1 over a pH range from 5.0 to 9.0 even though this mutant apparently lacks Cah1 expression in air. Although the presence of pCA1 apparently gives some minor benefit at very low CO(2) concentrations, the characteristics of this Cah1 null mutant demonstrate that pCA1 is not essential for function of the CO(2)-concentrating mechanism or for growth of C. reinhardtii at limiting CO(2) concentrations.